THE ROLE OF FINANCIAL REPORTING IN BUSINESS COMMUNICATIONS FOR SUPPORTING MANAGERIAL DECISION-MAKING - HOLOVAY, Nadiia; SYSOIEVA, Inna; KRASUTSKYI, Serhii; VIKARIY, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the study of the role of financial reporting in supporting the process of management decision-making in the modern business environment, which is characterized by a high level of dynamism and globalization. The authors emphasize the importance of quality characteristics of financial reporting, such as reliability, completeness of coverage, relevance and objectivity, to ensure the effectiveness of enterprise management. The key indicators of financial reporting that affect the assessment of liquidity, solvency, profitability and business activity of the enterprise are considered.Special attention is paid to the implementation of International Financial Reporting Standards (IFRS) as a tool for harmonizing accounting approaches, which ensures transparency and comprehensibility of financial data for interested parties regardless of their geographic location. The importance of IFRS for increasing trust in financial reporting, simplifying access to international capital markets and adapting to the conditions of a globalized economy is analyzed.Particular emphasis is placed on the latest trends in the field of financial reporting, in particular, the introduction of management reporting in real time, which allows managers and stakeholders to receive operational information for decision-making in conditions of dynamic changes. The benefits of using modern technologies such as financial process automation, big data analytics and artificial intelligence to ensure accuracy and timeliness of reporting are noted.The key challenges that ensure the implementation of real-time reporting are considered, including making significant investments in information technology, ensuring cyber security and data protection. The risks associated with manipulations in financial statements and the importance of maintaining trust in reporting as a source of objective information were discussed.The conclusions emphasize the need to develop financial reporting as an important strategic management tool that increases the competitiveness of enterprises, adapts to market changes and achieves sustainable business development.Prospects for further research related to improving reporting approaches, integrating innovative technologies, and harmonizing accounting standards to support effective management decision-making.The article explores the role of financial reporting as a key element of business communications, ensuring transparency, trust, and efficient information exchange among business process participants. Its impact on supporting managerial decision-making, strategic planning, interaction with regulatory bodies, and other stakeholders is analyzed. The significance of reporting in forming well-grounded managerial decisions and strengthening business relations is outlined.
Keywords: financial reporting; management decisions; quality characteristics; International Financial Reporting Standards (IFRS); real-time reporting; automation of financial processes; globalization; accounting; financial analysis; Indicators; business communications